Qualitative analysis of two reconstruction techniques and their application in dentistry - Nonato, Luis Gustavo; Minghim, Rosane; Shimabukuro, Milton Hirokazu [UNESP] (SPIE, the international society for optics and photonics, 2000)
Although visualization in the field of dentistry has some of the same requirements as the medicine field, the differences in goal demand specific approaches. This paper reports on the implementation of two fundamentally different approaches to reconstruction of structures from planar cross sections and their application to dentistry data. One of the approaches was an implementation of a distance-based sampling technique, and the other is a new algorithm, based on the Delaunay triangulation. Both were tested using contour data of teeth and the results are compared here in the light of the target applications, which are teaching and training dentistry, as well as simulation of dental procedures and illnesses. Widely mentioned problems encountered in local reconstruction methods such as marching cubes for these cases are clearly illustrated in this paper, and a very satisfactory alternative is given. © 2000 SPIE and IS&T.